Infeksi Protozoa Usus Pada Anak Sekolah Dasar Di Indonesia: Tinjauan Naratif Tentang Pengetahuan Dan Faktor Resiko - Ipan Jeremia Manik; Anisa Nuraisa Jausal; Endah Setyaningrum; Jhons Fatriyadi Suwandi (CV. Jasa Sukses Abadi, 2026)
Intestinal protozoan infections are a prevalent public health problem among primary school children in Indonesia, contributing significantly to acute and chronic diarrhoea, malnutrition, and anaemia, which ultimately reduce cognitive performance and learning ability. This literature review aims to identify patterns of knowledge, hygiene behaviour, and environmental and socio-economic factors that serve as key risk predictors for intestinal protozoan infections in this population. Various cohort and cross-sectional studies in Indonesia highlight Giardia duodenalis, Entamoeba histolytica/dispar, and Blastocystis spp. as the dominant pathogens, with the highest prevalence in areas with poor sanitation, limited access to clean water, and high population density. Behavioural factors include a lack of consistency in handwashing with soap (HWS), nail hygiene, and healthy snacking habits, despite the widespread implementation of health education interventions. Multivariate analysis of the literature review indicates a synergistic interaction between low hygiene knowledge and inconsistent practices, coupled with suboptimal environmental sanitation, limited potable water infrastructure, and low socioeconomic status as key determinants. Overall, these findings emphasise the need for a multidimensional intervention approach that integrates behaviour-based education, improved sanitation infrastructure, and socio-economic support to reduce the burden of intestinal protozoan infections in primary school children in Indonesia. Further prospective research is needed to validate causality and evaluate the effectiveness of interventions.